2012
DOI: 10.1016/j.socnet.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent aggression: The role of peer group status motives, peer aggression, and group characteristics

Abstract: Recent studies of youth aggression have emphasized the role of network-based peer influence processes. Other scholars have suggested that aggression is often motivated by status concerns. We integrate these two veins of research by considering the effects of peer status motivations on subsequent adolescent aggression, net of their own status motivations, prior aggression, and peer behavior. We also explore different levels at which peer effects may occur, considering the effects of reciprocated and unreciproca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 60 publications
(75 reference statements)
4
60
0
3
Order By: Relevance
“…Status is not, however, merely a means to win resources, but is an end to itself. The majority of adolescents in our study felt that "being popular" was somewhat or very important, and status valuation predicts subsequent aggression and other risk behaviors ( Faris and Ennett, 2012;Sijtsema et al, 2009). Park and Burgess (1921, p. 30;quoted in Bothner et al, 2010a andBothner et al, 2010b) observed that "men work for wages…they will die to preserve their status.…”
Section: Discussionmentioning
confidence: 75%
“…Status is not, however, merely a means to win resources, but is an end to itself. The majority of adolescents in our study felt that "being popular" was somewhat or very important, and status valuation predicts subsequent aggression and other risk behaviors ( Faris and Ennett, 2012;Sijtsema et al, 2009). Park and Burgess (1921, p. 30;quoted in Bothner et al, 2010a andBothner et al, 2010b) observed that "men work for wages…they will die to preserve their status.…”
Section: Discussionmentioning
confidence: 75%
“…Bullying is a serious form of aggression since it has several adverse effects on the victimized students. Victims are likely to experience anxiety, depression, low selfesteem, mental and physical health problems, and isolation from peers (Faris and Ennett, 2012;McKenney et al, 2006). Furthermore, victimization might have negative consequences on students' school performance (Eisenberg et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It depends on the context in which individuals operate and the limits, boundaries and checks that are imposed on peer-to-peer interactions (Card and Hodges, 2006;Faris and Ennett, 2012;Hawkins et al, 2001;Salmivalli et al, 1996).…”
mentioning
confidence: 99%